The "Bonding Hypothesis": What it is, Why it Matters, and Why Latin America is Different - Schrage, Burkhard N. (Institutional Knowledge at Singapore Management University, 2004)
An emerging "bonding hypothesis" holds that a firm's geographic domicile may not determine its corporate governance destiny. Firms from countries with weaker corporate governance regimes can internationalize their legal (but not necessarily operational) presence by cross-listing their securities on overseas financial markets. They can "bond" with legal systems and enforcement policies in foreign corporate governance regimes providing stronger investor protection. Cross-listing to bond increases firm value by decreasing corporate misconduct, broadening the investor base, and lowering the cost of capital. We document evidence of cross-listing to bond with stronger legal systems and rule of law by more than 700 firms from 23 emerging-market countries cross-listing their securities on US financial markets from 1996-2002. We find that: 1) US cross-listing levels are lower for firms from Common Law countries providing stronger investor protection, but only in Common Law countries with weaker rule of law; and 2) US cross-listing levels are higher for firms from Civil Law countries providing weaker investor protection, but only in Civil Law countries with stronger rule of law. Emerging-market firms exhibit behavior consistent with bonding hypothesis considerations and cross-list as a commitment to a more rigorous corporate governance regime, but the behavior is contingent and depends on examination of both legal system and rule of law effects individually and in interaction. Our empirical results highlight the importance of broadening investigating of firm internationalization to consider legal dimensions. Firms have discretion to choose foreign corporate governance regimes with less or no regard to where their operations are located.